Palaeontology of the early cretaceous non-marine molluscan assemblages from the Sao Khua formation in Nong Bua Lamphu, Phu Wiang and Sahat Sakhan areas, Northeastern Thailand - Sakboworn Tumpeesuwan (Chulalongkorn University, 2013)
Thesis (Ph.D.)--Chulalongkorn University, 2010